Medical racism - Ramšak, Mojca (Array, 2020)
The article analyses key examples of unethical medical experimentation on humans. The first part deals with racism, its ideology, and connectedness with concepts of medical racism. Concepts of the race that first emerged during the colonial expansion were defined by following their origins and function and not the philosophical thought. The second part builds upon the autonomy of patients. It includes the right to informed consent, protection of privacy, right of confidence, and persons with limited autonomy, all from a historical perspective on medical racism. In this section, the selected cases of medical racism show that the development of legal regulations and ethical norms importantly influenced the medical practice and the protection of subjects. The historical evidence also witnesses that even if the formal protection existed, there were deviations from it. The deviations were closely related to socio-political regulation and the rapid development of medicine that was a step before ethical norms. Additionally, war crimes against humanity were connected with personal ideological orientations of doctors whose racist, discriminatory beliefs were far beyond medical ethics and the purpose of medical practice. In the end, the article deals with the questions whether the results from unethical and unscientific experiments should be used and in what way medical racism endangers vulnerable groups today.